"A Suggested Model for Predicting Financial Default in Private Commercial Banks in Syria (An Applied Study on a Sample of Private Commercial Banks during the Period 2014-2017)" (Journal of Hama University, 2021)
The study aims to propose a model consisting of a set of financial ratios that can be used to predict the default of banks and distinguish between troubled banks and non- troubled banks, in order to identify the situation of these banks at an early date to allow interested parties as well as regulators to take appropriate corrective action if necessary. In this study, we rely on the method of discriminatory multivariate analysis to determine the ability of the proposed model to predict financial default and then distinguish between non-defaulted banks, using a set of eight financial ratios to select the best ratios to form the discriminatory equation and build the model, the data of these ratios were obtained from the financial statements published on the Damascus Securities Exchange during the period (2014,2017).The following model was obtained:   Z = -0.288 X2 + 0.149 X6 + 20.653 X8 – 22.155And the following results were obtained:The proposed two-component model (x2: Net profit/shareholders' equity, x6: Number of shares traded/number of ordinary shares, x8: Share market value/book value per share) is capable of predicting financial default a year before it occurs and is able to distinguish between troubled and non- troubled banks with accuracy of (100%).